Stalled at Friendship Station: Under Ancient Desert Skies, the Socialist Silk Road, and Cinematic Collaboration on the Eve of the Sino‐Soviet Split - TYERMAN, EDWARD (The Russian review (Stanford), 2021)
This article contributes to an emerging history of socialist world cinema by uncovering the forgotten story of a Sino‐Soviet cinematic collaboration from 1957–58: a film expedition that travelled the route of a proposed railway line linking Almaty in Kazakhstan, via Xinjiang, to Lanzhou in western China. At the height of the Sino‐Soviet “honeymoon” in the 1950s, this 2,800km “Road of Friendship” was celebrated as a revival of the ancient Silk Road for an age of industrialized, international socialism. Co‐produced by the Moscow and Shanghai scientific‐popular film studios, the film had two directors, the Soviet veteran Vladimir Shneiderov and the Chinese novice Qin Zhen. The film they created appeared under two names: while its Chinese title, Almaty‐Lanzhou (Alamutu‐Lanzhou), spoke in neutral tones of connection and modernization, the Russian title, Under Ancient Desert Skies (Pod nebom drevnikh pustyn'), evoked the exotic allure of a motor expedition along the traces of the Silk Road. My excavation of the Road of Friendship and the film that celebrated its construction offers a case study in the aspirations and limitations of Sino‐Soviet collaboration in the mid‐1950s. In particular, the history of both railway and film illuminate the role of Xinjiang as a frontier region where the ideals of internationalist collaboration confronted a longer history of imperial contestation between the Russian and Chinese states in Central Asia. Grounded in archival materials, this reconstruction of the project foregrounds both the politics and the poetics of collaboration: both the production history of the film, and the way that the film itself stages and performs its own ideals of collaborative “friendship.” Collaboration, it becomes clear from the film and its production materials, was both an important ideal and a fraught business. The Road of Friendship itself, meanwhile, fell victim to the Sino‐Soviet Split of the early 1960s. The two sides were supposed to connect at the town of Druzhba (Dostyk, “Friendship”) on the Sino‐Soviet border, but the Chinese branch only reached Druzhba in 1990—just in time for the collapse of the USSR. Today the Lanzhou—Almaty rail route constitutes a central link in China's Belt and Road infrastructure initiative, another reimagining of the Silk Road for twenty‐first‐century global capitalism.